A decision that is long overdue - Alang Md Rashid, Nahrul Khair (The New Straits Times Press (Malaysia) Berhad, 2010)
Any announcement on a nuclear power programme evokes reaction and debate, which is a good thing. A good debate can educate the public and their opinions can influence any decisions.